ЖОҚАРЫ ОҚЫЎ ОРЫНЛАРЫ ТАЛАБАЛАРЫНЫҢ ДӨРЕТИЎШИЛИК КӨЗҚАРАСЫН РАЎАЖЛАНДЫРЫЎ - Уразимова, Т.В. (FAN va JAMIYAT, 2016)
The article is devoted to the modern content and role of educational process, because modern society has increased attention to the problem of formation of a fully developed, spiritually rich and creative personality. Human personality and his spiritual and moral character are formed primarily in the process of education. Aesthetic education plays here a great role contributing to enhance the development of philosophy, intellectual and creative potential of the individual. Therefore, the process of education should be based on creating conditions for education of creative personality, ready for a dialogue, collaboration and co-creation in various spheres of life.